(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this paper, the noise-correcting Reed-Solomon code is investigated and modeled to provide an increase in noise immunity in a digital television system of the DVB-T2 standard. Theoretical and practical algorithm of functioning of the Reed-Solomon noise-correcting codec has been studied. The error-correcting Reed-Solomon code in the DVB-T2 standard digital television system with the developed interactive computer simulation program in the Matlab/Simulink programming language, the dependence of the number of errors on the error probability for the noise-correcting Reed-Solomon code is modeled and investigated.